2017
DOI: 10.3389/fmicb.2017.02221
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adhesion of Listeria monocytogenes Strains to Abiotic Surfaces under Cold Stress

Abstract: Food contamination by Listeria monocytogenes remains a major concern for some food processing chains, particularly for ready-to-eat foods, including processed foods. Bacterial adhesion on both biotic and abiotic surfaces is a source of contamination by pathogens that have become more tolerant or even persistent in food processing environments, including in the presence of adverse conditions such as cold and dehydration. The most distinct challenge that bacteria confront upon entry into food processing environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 30 publications
3
24
0
7
Order By: Relevance
“…The elongation and filamentation of L. monocytogenes is a unique finding in the present study. Numerous studies have reported the elongation and filamentation of L. monocytogenes cells in the presence of several environmental stress conditions such as temperature, salt, pH, and antimicrobials [76][77][78]. The elongation of L. monocytogenes cells by UA-CS NPs in the present study might be due to the inhibition of cell division.…”
Section: Effect Of Ua-cs Nps On Cell Morphologymentioning
confidence: 51%
“…The elongation and filamentation of L. monocytogenes is a unique finding in the present study. Numerous studies have reported the elongation and filamentation of L. monocytogenes cells in the presence of several environmental stress conditions such as temperature, salt, pH, and antimicrobials [76][77][78]. The elongation of L. monocytogenes cells by UA-CS NPs in the present study might be due to the inhibition of cell division.…”
Section: Effect Of Ua-cs Nps On Cell Morphologymentioning
confidence: 51%
“…Common contaminated foods are smoked fish, cold cuts and fresh cheese. Together with this low temperature replication ability, this bacterium enhances its hydrophilicity and induces biofilm status as a response to cold temperatures, increasing its attachment to surfaces and its resistance to cleaning procedures in many food factories ( Zhang et al, 2016 ; Lee et al, 2017 ). The eradication of this pathogen in the food industry is further complicated by its resistance to treatments up to 60°C ( Møretrø et al, 2017 ).…”
Section: Health Aspects Associated With Food Industry Biofilmsmentioning
confidence: 99%
“…A biofilm is a population of bacterial cells attached to each other or a surface and enclosed by a self-produced matrix of extracellular polymeric substances (EPS) (proteins, polysaccharides, and extracellular DNA) [71]. The matrix is a nutrient reservoir, facilitates adhesion, acts as a protective barrier against heat and desiccation, heavy metals, ultraviolet rays, acids, and also inhibits the permeation of antimicrobial agents by restricting their diffusion potentials [72,73].…”
Section: Persister Cells and Biofilm Formationmentioning
confidence: 99%